Editorial [Hot Topic: Nucleic Acid Metabolism and Human Disease (Guest Editor: Luis G. Brieba)] - Brieba, Luis G. (Current Topics in Medicinal Chemistry, 2008)
DNA is our “blueprint” and it can be envisioned as a pristine code that contains the instructions for life. However, DNA has inherent problems to be maintained as a pristine code. DNA has to be replicated with almost perfect accuracy, and as an organic molecule it can react with chemical substances of the cellular milieu. The DNA polymerases that replicate our DNA are far from perfect. Our nuclear replicative DNA polymerases, DNA polymerases δ and ε, make a mistake in approximately 5x105 of their incorporation events, although this accuracy is enormous, it is compromised along the replication of the billions of base pairs that comprise our genome. DNA polymerase γ, our replicative mitochondrial DNA polymerase, makes a mistake in approximately 1x104 attempts; however we are born with a set of mitochondrial DNA molecules that have to be maintained nearly intact during our life. Although the fidelity of DNA polymerases can seem reasonable, DNA is prone to react with chemical substances that can alter its coding potential. For instance, guanosine can react with reactive oxidative species to be converted to 8-oxo guanosine, and when a normally faithful replicative DNA polymerase, like T7 DNA polymerases encounters 8-oxo guanosine as a template, it will misincorporate dATP in approximately one of three events. In order to maintain DNA as the pristine code, humans have evolved a series of metabolic pathways that maintain its integrity, both in the nuclei and in the mitochondria. This issue of Current Topics in Medicinal Chemistry addresses the interplay between “Nucleic Acids Metabolism and Human Disease”. The first review provides a brief summary of human template dependent DNA polymerases, with emphasis in their structure and their association with human diseases. In the second review, Hector Viadiu revisits the structural significance of the transcription factor p53 as a tumor suppressor. All the effort to understand the structure of p53 rests in the goal to restore wild type p53 activity by rational efforts, as p53 plays a pivotal role in cancer development. Mitochondria are the organelle responsible to synthesize ATP, the molecule used as the energy source by the cell. The team leaded by Xochilt Perez-Martínez reviews the state of the art knowledge in protein synthesis and assembly at the mitochondria, and the link of specific mutations of the mitochondria macromolecular assemblies involved in translation and protein folding with mitochondrial disorders. The team leaded by Rafael Montiel reviews the link between mitochondrial DNA mutations and cancer. This review contains a comprehensive list of somatic mitochondrial mutations that have been observed in cancer tissues. In the fifth review, Felix Recillas-Targa discusses the links between epigenetic regulation and novel therapeutic approaches in cancer. The last two reviews highlight the role of DNA as a therapeutic agent. Luis M. Alvarez-Salas reviews the role of therapeutic nuclei acids, such as nucleosides, nucleotides, ribozymes, antisense aptamers, and small interfering RNA, with an emphasis in those therapeutic nucleic acids that are in clinical trials in cancer and viral diseases. Anna Arola and Raul Vilar discuss the use of small molecules that promote the stabilization of quadruplex DNA. The stabilization of quadruplex DNA opens the possibility to be use as a potential target for rational drug design against cancer. Finally, I thank Dr. Allen Reitz for the opportunity to serve as a Guest Editor of this issue and to the authors whom kindly wrote their insightful contributions.